Utilization of Striped Snakehead Fish and Tofu Dregs in Making Nugget - Ayu, Dewi Fortuna; Sapika, Nadia; Hamzah, Faizah (Universitas Pattimura, 2022)
This research aimed to get the best formulation of striped snakehead fish and tofu dregs nuggets based on Indonesian National Standard SNI 7758-2013. A completely randomized design was conducted with five treatments, which were the ratios of striped snakehead fish and tofu dregs, such as 90:10, 85:15, 80:20, 75:25, and 70:30, and three replications. Data showed a significant effect of the ratio of striped snakehead fish and tofu dregs on moisture, ash, protein, crude fibre content, and descriptive analysis in sensory evaluation and overall hedonic test on nugget. The nugget from the ratio of striped snakehead fish and tofu dregs 90:10 was the best formulation with a moisture content of 64.66%, an ash content of 1.04%, protein content of 9.69%, a fat content of 0.65%, and crude fibre content of 0.61%. The descriptive sensory analysis showed that the nugget had a white color inside and a golden yellow outside, flavored with striped snakehead fish, a bit chewy, and had a striped snakehead fish taste.